Empirical study of National Strategy for Financial Education of India (2020 – 2025) with special reference to awareness of Insurance & Pension Plans - Pimple, Mr. Sachin; Peshori, Dr. (CA) Kishore; Peshori, Dr. (CA) Kishore (The journal of contemporary issues in business and government, 2022)
The Organisation for Economic Co-operation and Development (OECD) and its International Network on Financial Education (INFE) is working constantly for the understanding the level of Financial Literacy (FL) and measures to improve it at global level. Government of India has also followed the definition of FL provided by OECD/INFE and further working on the lines of improvement of FL level in the country as the improved financial level of countrymen will also support the development of economy. Indian Government has made its vision very clear about FL that every Indian shall be financially literate and empowered. To achieve this vision Government of India has designed National Strategies for FE time to time. The current National Strategy for Financial Education (NSFE) is designed for the period of five years from 2020 to 2025. This NSFE (2020-2025) policy is designed with a holistic approach to make Indian citizen aware about financial education (FE) related to banking services, financial market services, loan facilities, insurance cover, pension plan the working of all these. Strategy also discusses about the strengthening of banking ombudsmen and other consumer forums for the protection of consumer rights effectively. This study is an attempt to understand the effectiveness of the efforts of government to reach to common people to improve their FL level. Study is conducted in Mumbai Metropolitan Region area to know how the people of the financial capital of the country are equipped with FE. The Study is however, limited to understand the awareness level of people only about insurance and pension related concepts.